2016
DOI: 10.1371/journal.pone.0158727
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospitalized Exacerbations and Mortality in Chronic Obstructive Pulmonary Disease

Abstract: Background and AimExacerbations of chronic obstructive pulmonary disease (COPD) carry significant consequences for patients and are responsible for considerable health-care costs—particularly if hospitalization is required. Despite the importance of hospitalized exacerbations, relatively little is known about their determinants. This study aimed to analyze predictors of hospitalized exacerbations and mortality in COPD patients.MethodsThis was a retrospective population-based cohort study. We selected 900 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 48 publications
6
59
0
3
Order By: Relevance
“…DM is a risk factor for AECOPD 18. Patients with DM and AECOPD frequently (50%–80% of patients) presented with hyperglycemia during their hospital stay and experienced longer hospital stays and higher mortality rates than patients without DM 19,20.…”
Section: Discussionmentioning
confidence: 99%
“…DM is a risk factor for AECOPD 18. Patients with DM and AECOPD frequently (50%–80% of patients) presented with hyperglycemia during their hospital stay and experienced longer hospital stays and higher mortality rates than patients without DM 19,20.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found higher odds for older age, 51,53,54 severity, 51,55 comorbidities such as HF (in COPD patients), cancer, renal failure, 55 depression 56 and diabetes. 53 For COPD, Fidahussein et al 54 also found an association for LOS. Not all studies reported sex differences, although some agreed with our finding of higher odds for males for both conditions.…”
Section: Comparison With Previous Workmentioning
confidence: 91%
“…Thorough assessment of these patients on admission, using laboratory tests, comorbidities assessment, and objective instruments to quantify dyspnea and symptoms (mMRC, VAS and CAT) is essential to reduce hospital stay, prevent readmission and decrease mortality. 36,37 Patients admitted due to eCOPD are a heterogeneous group that can be grouped into three clusters as described, although we did not find an association between these clusters and the outcomes of hospitalization. Studies with a larger sample of patients are needed to confirm the findings reported here and to relate them to the outcomes of hospitalizations due to eCOPD.…”
Section: Results As N (%) or ± Sd (Min-max)mentioning
confidence: 63%